Awareness of mother to child HIV transmission among women attending antenatal clinic, SMIMER, Surat (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
The study was conducted among 946 women attending antenatal clinic in SMIMER teaching hospital during 2008 to know their awareness regarding various aspects of mother-to-child transmission (MTCT) of HIV and it was found that though the general awareness of HIV is high, awareness of MTCT and its prevention is low which need to be improved through focused IEC campaign. Background : More than 90% of HIV infections in children aged